Computing optimal policy in a timeless-perspective: An application to a small-open economy - Michel Juillard; Florian Pelgrin (Bank of Canada, 2007)
Since the contribution of Kydland and Prescott (1977), it is well known that the optimal Ramsey policy is time inconsistent. In a series of recent contributions, Woodford (2003) proposes a new methodology to circumvent this problem, namely the timeless perspective solution. However, one main limitation is that it is not yet empirically implementable. In this paper, we develop a new methodology to compute initial values of the Lagrange multipliers in order to implement the timeless-perspective solution. In so doing, we also provide a generalization of the Ramsey and timeless-perspective problems. We apply our results to a small-open economy model in Canada.
Keywords: C6; E5; E6; 330; Monetary policy framework; Geldpolitik; Zeitökonomie; Dynamisches Modell; Kanada